Fitness is a determinant of the metabolic response to endurance training in adolescents at risk of type 2 diabetes mellitus. (7th March 2015) - Sénéchal, Martin; Rempel, Meaghan; Duhamel, Todd A.; MacIntosh, Andrea C.; Hay, Jacqueline; Wicklow, Brandy; Wittmeier, Kristy; Shen, Garry X.; McGavock, Jonathan M.
Abstract : Objective: The purpose of this prospective cohort study was to determine whether changes in cardiorespiratory fitness are associated with the metabolic response to endurance training in adolescents at risk of type 2 diabetes mellitus (T2DM). Methods: Seventy‐three overweight and obese adolescents completed a 6‐month endurance exercise intervention. Total fat mass, trunk fat mass, visceral adipose tissue, and liver fat were assessed with dual energy X‐ray absorptiometry and magnetic resonance imaging spectroscopy. Results: The change in cardiorespiratory fitness with training was independently associated with reductions in BMI z ‐score ( β  = −0.09; P  = 0.006), total fat mass ( β  = −1.40; P  = 0.007), trunk fat mass ( β  = −0.70; P  = 0.01), and liver fat ( β  = −1.80; P  = 0.053). Adolescents within the highest tertile of change in fitness were 4.67 (95% CI: 1.15‐13.73; P  = 0.03), 11.90 (95% CI: 2.37‐59.77; P  = 0.002), and 6.21 (95% CI: 1.14‐33.99; P  = 0.035) times more likely to experience decreases in body weight, BMI, and liver fat compared with adolescents in the lowest tertile. Conclusions: The changes in adiposity and hepatic triglyceride content in response to endurance training are significantly related to the increase in cardiorespiratory fitness in adolescents at risk of T2DM.